Analysis of Factors Influencing Intention to Reuse Stock Applications in Greater Jakarta - Fatimatuzzahroh Fatimatuzzahroh; Eka Dasra Viana (Green Publisher Indonesia, 2025)
The number of Single Investor Identification (SID) has grown rapidly in the previous five years. One of the factors that supported this trend was the emergence of stock apps that offered advantages such as accessibility, ease of transactions, and portfolio monitoring. However, there are still obstacles related to the use and utilization of stock applications within the community. This study aimed to analyze the effect of perceived ease of use, perceived usefulness, perceived security and privacy, and trust on the intention to reuse stock applications in Jabodetabek. The data sources consisted of primary data in the form of questionnaires and secondary data in the form of literature studies, with sampling techniques using non-probability sampling through the quota sampling method, with 230 respondents. Data processing and analysis methods in this study included descriptive analysis and SEMPLS. The results showed that perceived ease of use, perceived usefulness, trust, and perceived security and privacy had a positive effect on intention to reuse, while gender had no moderating effect on the use of stock applications.